Tekanan Kerja dan Kesihatan Mental dalam Kalangan Pekerja Perubatan Semasa Pandemik COVID-19 - Auni Faseeha Abdul Razak; Nurazwa Ahmad; Nor Kamariah Kamaruddin; Ahzilah Wahid (Research in Management of Technology and Business, 2022)
In this new norm, medical workers working in high-risk areas of COVID-19 are reported to have an increased risk of developing adverse effects on mental health problems such as depression, anxiety, insomnia, and distress. In addition, for members of the medical sector, they usually experience heavy workloads, long working hours and high levels of stress during work routines and this causes mental health risks for the workers. Thus, the situation of the COVID-19 pandemic can worsen the level of work pressure for staff in the medical field directly affecting mental health problems. This study aims to examine the level of work stress and mental health and the relationship between work stress and mental health problems among medical workers during the COVID-19 pandemic. This study is quantitative in nature by using a questionnaire as a research tool distributed through Google Form and 102 responses have been received from medical workers around Alor Setar, Kedah. Data was analyzed using SPSS software for descriptive analysis and Pearson correlation. The findings of the study show a moderate level of work stress and mental health among medical workers. Next, there is a positive and significant relationship for both variables showing that increased work stress conditions have a high correlation with medical workers’ mental health problems. Full support measures need to be intensified by all parties to support the initiatives of the medical sector so that it can continue to provide excellent, quality and continuous services in curbing the spread of the COVID-19 epidemic which is clearly capable of threatening the lives of every individual in Malaysia and in the world